Hospital waiting time : the forgotten premise of healthcare service delivery? - Pillay, M. S.; Mohd Ghazali, Roslan Johari; Abd. Manaf, Noor Hazilah; Assari Abdullah, Abu Hassan; Abu Bakar, Azman; Salikin, Faisal; Umapathy, Mathyvani; Ali, Roslinah; Bidin, Noriah; Wan Ismail, Wan Ismefariana (Emerald, 2011)
Purpose – This is a national study which aims to determine the average waiting time in Malaysian public hospitals and to gauge the level of patient satisfaction with the waiting time. It also aims to identify factors perceived by healthcare providers which contribute to the waiting time problem. Design/methodology/approach – Self-administered questionnaires were the main method of data collection. Two sets of questionnaires were used. The first set solicited information from patients on their waiting time expereince. The second set elucidated information from hospital employees on the possible causes of lengthy waiting time. The questionnaires were administered in 21 public hospitals throughout all 13 states in Malaysia. A total of 13,000 responses were analysed for the patient survey and almost 3,000 were analysed for the employee survey. Findings – The findings indicate that on average, patients wait for more than two hours from registration to getting the prescription slip, while the contact time with medical personnel is only on average 15 minutes. Employee surveys on factors contributing to the lengthy waiting time indicate employee attitude and work process, heavy workload, management and supervision problems, and inadequate facilities to be among the contributory factors to the waiting time problem. Social implications – Public healthcare in Malaysia is in a state of “excess demand”, where demand for subsidised healthcare far outstrips supply, due to the large fee differential between public and private healthcare services. There is a need for hospital managers to reduce the boredom faced by patients while waiting, and to address the waiting time problem in a more scientific manner, as has been carried out in other countries through simulation and modelling techniques. Originality/value – Healthcare organisations are keen to address their waiting time problem. However, not much research has been carried out in this area. The study thus fills the lacuna in waiting time studies in healthcare organisations